2019
DOI: 10.1029/2018gl081284
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Utilization of Volatile Fatty Acids and Alcohols in Hydrothermally Altered Sediments in the Guaymas Basin, Gulf of California

Abstract: Volatile fatty acids (VFAs) and alcohols are key intermediates of anaerobic carbon metabolism, yet their biogeochemical cycling remains poorly constrained in hydrothermal systems. We investigated the abundance, stable carbon isotopic composition, and metabolic cycling of VFAs and alcohols to elucidate their generation and utilization pathways in hydrothermally influenced sediments (4 °C to 90 °C) from the Guaymas Basin. Acetate (up to 229 μM) and methanol (up to 37 μM) were abundant in porewaters. The δ13C val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…Although methanol was previously considered as the noncompetitive substrate for methanogen (Oremland and Polcin ), much higher oxidation rates than the methanogenesis rates indicated methanol was predominantly metabolized by nonmethanogenic processes (e.g., sulfate‐reducing bacteria). This is consistent with recent studies (Zhuang et al ; Zhuang et al ), which demonstrated that the metabolism of methanol by methanogen vs. sulfate‐reducing bacteria differed from sites and habitats. In contrast, the turnover of methylamine to methane and CO 2 were comparable at deeper depth of ROV2 and ROV3, suggesting both methanogenic and nonmethanogenic processes were responsible for the utilization of methylamine.…”
Section: Discussionsupporting
confidence: 93%
“…Although methanol was previously considered as the noncompetitive substrate for methanogen (Oremland and Polcin ), much higher oxidation rates than the methanogenesis rates indicated methanol was predominantly metabolized by nonmethanogenic processes (e.g., sulfate‐reducing bacteria). This is consistent with recent studies (Zhuang et al ; Zhuang et al ), which demonstrated that the metabolism of methanol by methanogen vs. sulfate‐reducing bacteria differed from sites and habitats. In contrast, the turnover of methylamine to methane and CO 2 were comparable at deeper depth of ROV2 and ROV3, suggesting both methanogenic and nonmethanogenic processes were responsible for the utilization of methylamine.…”
Section: Discussionsupporting
confidence: 93%
“…It should be noted, however, that most of these studies focused solely on the Atlantic Ocean and mainly on shallow, aerobic sub‐surface waters, with only one study investigating a gradient of up to 500 m depth (Dixon and Nightingale, 2012). Estimates of methanol levels in coastal area sediments range between 0.3 μM and over 100 μM in environments as diverse as the Orca Basin in the Gulf Mexico, East Japan Sea and the South China Sea (Yanagawa et al ., 2016; Zhuang et al ., 2014; 2019a,b). In these studies, methanol concentrations were found to increase with depth, with the lowest concentrations close to the seafloor and the highest concentrations at depths of 10–20 m below the seafloor.…”
Section: Sources Of Methanol In Marine Sedimentsmentioning
confidence: 99%
“…In these studies, methanol concentrations were found to increase with depth, with the lowest concentrations close to the seafloor and the highest concentrations at depths of 10–20 m below the seafloor. This increase in methanol with depth is attributed to higher methanol turnover to CO 2 near the sediment‐water column interphase (Zhuang et al ., 2019a,b). Table 1 gives an overview of marine anaerobic sediments where methanol concentrations have been measured.…”
Section: Sources Of Methanol In Marine Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, acetate oxidation has been used as an indicator of organic carbon decomposition in anoxic sediments (Finke et al, 2007;Sørensen et al, 1981). Although much attention has been paid to the importance of acetate in marine sedimentary systems (e.g., Zhuang, Montgomery, & Joye, 2019;Zhuang, Montgomery, Samarkin, et al, 2019), the cycling of acetate in the oceanic water column remains largely unconstrained (Ho et al, 2002;Wu et al, 1997;Wu & Scranton, 1994).…”
Section: Introductionmentioning
confidence: 99%